Health benefits and toxicities of the consumption of Centella Asiatica: a scoping review - Abd. Ghani, Muhammad Nurhakkim; Azahari, Nuraniza (IIUM Press, 2022)
Introduction: Centella Asiatica is a well-known herb used in alternative medicine. Despite being widely used, few papers investigated the health benefits of C. asiatica in depth. Other than concerning its up-to-date benefits, the toxicity of C. asiatica needs to be addressed as well. As previous studies did not show any toxicities of this herb in detail, further investigation is necessary. Hence, the main objective of this review is to investigate the benefits and toxicities of the consumption of Centella Asiatica. Methods: A scoping review was conducted according to the Arksey and O’Malley framework in two different phases: primary phase using electronic databases such as PubMed, Scopus, ResearchGate, and Google Scholar, and a secondary phase known as manual literature search. Results: Finally, 21 articles were included in the review. The health benefits of C. asiatica included neuroprotective, antihyperglycemic, anti-cancer, antioxidant, gastroprotective, nephroprotective, hepatoprotective, antihypertensive, anti-inflammatory, anxiolytic and antidepressant, and antiepileptic benefits. Unfortunately, all the papers did not discuss the toxicities of C. asiatica although two of them mentioned the positive herb-drug interactions of C. asiatica. Within the themes extracted from all reviewed studies, a neuroprotective benefit was the most largely mentioned with some of the chemical components of C. asiatica such as asiatic acid (AA) being primarily investigated in some papers. Conclusions: All the studies mainly investigate the same areas of health benefits of C. asiatica while some research discovers new areas, particularly in mental-related conditions. This study evaluates the breadth of information contained in the available literature and identifies the potential for a future systematic evaluation of specific updated health benefits or toxicities that have yet to be examined due to a lack of data.